2021
DOI: 10.3389/fimmu.2020.621757
|View full text |Cite
|
Sign up to set email alerts
|

Warburg Effect Is a Cancer Immune Evasion Mechanism Against Macrophage Immunosurveillance

Abstract: Evasion of immunosurveillance is critical for cancer initiation and development. The expression of “don’t eat me” signals protects cancer cells from being phagocytosed by macrophages, and the blockade of such signals demonstrates therapeutic potential by restoring the susceptibility of cancer cells to macrophage-mediated phagocytosis. However, whether additional self-protective mechanisms play a role against macrophage surveillance remains unexplored. Here, we derived a macrophage-resistant cancer model from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 80 publications
0
23
0
Order By: Relevance
“…The later stages of cancer are associated with well-known cancer hallmarks [ 86 ] including induction of angiogenesis to feed the growth of cancer cells [ 87 , 88 ], activation of metastasis driven by the epithelial-to-mesenchymal transition (EMT) [ 89 , 90 , 91 ], evasion from the immune surveillance, and formation of the tumor microenvironment [ 92 , 93 , 94 , 95 , 96 , 97 ].…”
Section: Introductionmentioning
confidence: 99%
“…The later stages of cancer are associated with well-known cancer hallmarks [ 86 ] including induction of angiogenesis to feed the growth of cancer cells [ 87 , 88 ], activation of metastasis driven by the epithelial-to-mesenchymal transition (EMT) [ 89 , 90 , 91 ], evasion from the immune surveillance, and formation of the tumor microenvironment [ 92 , 93 , 94 , 95 , 96 , 97 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant glycolysis is commonly associated with proinflammatory responses and immune evasion in the TME [37,44]. Recent studies showed that YBX1 regulated programmed death ligand 1 (PD-L1) expression to mediate immune escape in prostate cancer [45], and the infiltrating cluster of differentiation 4-positive (CD4+) T cells promoted the growth of renal cell carcinoma via modulating transforming growth factor-β1 (TGFβ1)/YBX1/HIF2α signals [46].…”
Section: Discussionmentioning
confidence: 99%
“…Diverse evidence suggests that the immune cells' response in the TME contributes to cancer cell survival and growth [49]. Interestingly, this abnormal metabolic profile has been pointed out as one of the factors which support immune evasion to tumor cells and promote tumor progression [50][51][52][53]. What justified this fact is that, as cytoplasmic is produced, lactate is released in the extracellular microenvironment by monocarboxylate transporters (MCTs), leading to pH reduction and to TME acidification [54,55].…”
Section: E -Evolutionmentioning
confidence: 99%